ANALISIS YURIDIS HAK DAN KEWAJIBAN WARGA NEGARA ATAS PENDIDIKAN MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL - Sara Tambun; Goncalwes Sirait; Janpatar Simamora (Visi Sosial Humaniora, 2020)
Education is an important issue and issue that the nation and the state of Indonesian are facing this time. Besides being important, being able to experience education is also a right for everyone. Lack of education in Indonesia can be seen in the Date Release of the Education For All (EFA) Global Monitoring Report 2011: Education Development Index wich UNESCO. Indonesia in year 2011 is 0,934 value is what puts Indonesia at posision 69 of 127 countries in the world. the causes could be the result of this lack of special attention to the aducation of the country to a greater extent in areas that really need  the attention of both the regional and the central goverments and not escape from the role of parents and families in not obstructing an increased education.